Exploring the Influence of Globalization on Digital Pedagogy and Access in Higher Educational Institutes(Karachi-Pakistan) (Journal of Asian Development Studies, 2025)
In a globalized world, digital techniques are one of the essential aspects that demand to be considered in every educational institute. Digital learning is very crucial to build up the collaboration, to develop quality education, and to make education achievable for everyone in the entire globe. Higher education requires technological integration to make its educational system more effective. Higher education must vitally learn to manage digital technologies within its institutions. The objective of this research is to identify the digital pedagogical techniques influenced by globalization and the challenges they face in implementing them in their universities. The study was conducted in universities in Karachi, Pakistan. The study's population is university faculty members. The data was collected from 6 faculty members of 3 universities. A qualitative approach was used in this study. The data was collected by semi-structured interviews. The thematic analysis procedures were used to analysethe data and topresent the study’s results. Themes were generated from respondents' responses to summarize the findings. The purposive sampling techniques were used in this study to choose sample size that has relevant knowledge and experience about digital learning at the higher education level. The findings of this study would be beneficial for educators, policymakers, and educational institutes. This study helps to increase awareness about digital learning techniques and their challenges so that they can better plan to improve the digital learning techniques at their educational institutions.